Treatment of Knee Osteoarthritis with Intraarticular Umbilical Cord-Derived Wharton's Jelly: A Case Report - Ashim Gupta; Hugo C. Rodriguez; Anish G. Potty; Howard J. Levy; Saadiq F. El-Amin III (MDPI AG, 2021)
We present the case of a 27-year-old male with grade II knee osteoarthritis (OA) that was intraarticularly injected with a 2 mL umbilical cord-derived Wharton's jelly (UC-derived WJ) formulation. The patients' baseline radiographs were taken and baseline numeric pain rating scale (NPRS), knee injury and osteoarthritis outcome score (KOOS), 7-point Likert scale, and a 36-item short form survey (SF-36) were recorded. The NPRS was re-recorded immediately after the injection, and at 24 h, 48 h, 1 week, 6 weeks, and at 3 months follow-up post-injection. The KOOS and 7-point Likert scale was re-recorded at the patients' 1week, 6 week, and 3month follow-up, and SF-36 was re-recorded at 3 months. A final set of X-rays were also performed at 3 months follow-up post-injection. No adverse effects from the injection were reported over the duration of the study. No significant difference nor progression in OA on X-rays compared to baseline was observed. NPRS decreased by 50% and the 7-point Likert scale increased to Extremely Satisfied. KOOS increased overall by 10% and the SF-36 overall change was 25%. These results indicate the potential application of UC-derived WJ in the treatment of knee OA. Larger, long term, non-randomized and randomized control trials are warranted to adequately assess the safety and efficacy of UC-derived WJ and ultimate clinical use.